Influence of place identity and place dependence on resilience towards Boko Haram insurgency among Maiduguri residents in Borno State, Nigeria - Mai Butu, Hauwa; Hashim, Ahmad Hariza; Ahmad, Nobaya (International Organization of Scientific Research, 2018)
Generally the importance of a place of residence becomes paramount to its habitants during lose and hard times. The economic viability of a place and self-reference to a place which depends on how individuals appreciate and express themselves in relation to their settings can increase residents’ consciousness of a specific place.It is in this vein that this study aim to examine whether place identity, place dependence, age,gender, length of stay, income and occupation influence sresilience toward Boko Haram insurgency in Maiduguri. Place attachment and resilience theory was used for this study. The study is unique in having investigated place identity, place dependence and other demographic characteristics on the survival of residents been troubled by terrorism. Though other studies have dealt mainly with areas of threat due to natural disasters,this present study,examine a particular neighbourhood that is subject to terrorist attacks for the past 8 years.This paper relies on a cross-sectional data, with a sample size of 383, using convenient sampling technique. The Pearson correlation analysis revealed significant and positive relationship between place identity and place dependence on resilience, while, age and length of stay indicated positive and insignificant.Income on the other hand, shows negative and insignificant relationship with resilience. The results of the Multiple Linear Regression analysis revealed that, place identity and place dependence are significant predictor of resident’s resilience towards Boko Haram insurgent. This is an indication that, in spite of the conflicts and casualties, the residents did not regard their neighborhood as being too hazardous and were holding on to the neighbourhood as a place they are identified with and depend on as a source of their livelihood.